2008
DOI: 10.1080/01674820802034631
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic stress disorder following childbirth: current issues and recommendations for future research

Abstract: This is the unspecified version of the paper.This version of the publication may differ from the final published version. Permanent

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
119
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(129 citation statements)
references
References 40 publications
7
119
0
2
Order By: Relevance
“…The one study to have used full DSM IV criteria, Alcorn et al (2010), found that 3.1% of women met criteria at 6 months after birth, after controlling for previous traumatic events, clinically significant anxiety and depression during pregnancy. These figures have led to international recognition of the importance of post-traumatic stress disorder following childbirth (Ayers, Joseph, McKenzie-McHarg, Slade, & Wijma, 2008). The findings reported in the current paper extend this focus by identifying variables that are predictive of initially birth related trauma and subsequent PTSD, thus possibly allowing for screening of at risk women.…”
Section: Discussionsupporting
confidence: 60%
“…The one study to have used full DSM IV criteria, Alcorn et al (2010), found that 3.1% of women met criteria at 6 months after birth, after controlling for previous traumatic events, clinically significant anxiety and depression during pregnancy. These figures have led to international recognition of the importance of post-traumatic stress disorder following childbirth (Ayers, Joseph, McKenzie-McHarg, Slade, & Wijma, 2008). The findings reported in the current paper extend this focus by identifying variables that are predictive of initially birth related trauma and subsequent PTSD, thus possibly allowing for screening of at risk women.…”
Section: Discussionsupporting
confidence: 60%
“…A number of authors have emphasized that preventive interventions should be based on the underlying psychological mechanism of traumatic stress symptoms (Ayers et al, 2008;Garthus-Niegel et al, 2013). However, the aetiology of these symptoms remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…As women are repeatedly exposed to the reminder of their trauma (i.e. their baby), this could also ameliorate or exacerbate their symptoms (Ayers et al, 2008).…”
Section: Introductionmentioning
confidence: 99%